Jeremy Boissevain (ed.): Revitalizing European Rituals samt Daniel de Coppet (ed.): Understanding Rituals - Hasse, Cathrine (Tidsskriftet Antropologi, 1993)
Jeremy Boissevain (ed.): Revitalizing European Rituals Daniel de Coppet (ed.): Understanding Rituals Anmeldes af Cathrine Hasse